A method to encourage and assess innovations in public tenders for infrastructure and construction projects. Issue 2 (25th January 2020) - Lenderink, Bart; Halman, Johannes I.M.; Boes, Hans; Voordijk, Hans
Abstract : Purpose: Stimulating innovation in projects can contribute to achieving policy goals, addressing societal challenges and meeting objectives within programs and projects. Despite their potential, innovations are rarely included in tender assignments and evaluated in the award of civil engineering projects. One explanation for this is the perceived difficulty in triggering and objectively assessing innovations in the awarding of projects. The aim of this paper is to develop, implement and evaluated a method to encourage and assess innovations in the awarding of bridge construction projects to address this problem. Design/methodology/approach: A design science research (DSR) approach is used to develop, implement and evaluate a method to trigger and assess innovations in tenders for bridge projects. DSR approaches are used to develop "well-tested, well-understood and well documented innovative generic designs, dealing with authentic field problems or opportunities" (van Aken et al., 2016). Findings: The findings show that the application of the developed method in a bridge project led to the inclusion of a broad range of innovations in the tender offers. Despite the broad support for the defined criteria, there were some differences in the way the criteria were interpreted by the public procurement team and by the tenderers. Despite these differences, no legal claims were filed in court. Practical implications: Further development and wider adoption of the method is likely to have a positive impact on the application of innovations in bridge projects. With some adjustments, the method would also be appropriate for other civil engineering and construction projects. Originality/value: This paper contributes to the discussion on how the terms innovation and innovativeness can be operationalized and used in the literature and practice. The developed method provides definitions for assessing the degree as well as the level of innovations in tenders for bridge projects. Further, it provides a way to rank innovations and determine the additional value of the offered innovations in terms of a notional reduction in tender price. Finally, it provides insights into how to encourage innovations through public procurement in civil engineering projects.